Aerobic exercise improves clearance of amyloid-β via the glymphatic system in a mouse model of Alzheimer's Disease - Shengxiang Liang; Huanhuan Liu; Xiuxiu Wang; Huawei Lin; Ling Zheng; Yusi Zhang; Lixin Peng; Saie Huang; Lidian Chen (Brain Research Bulletin)
Background: Aerobic exercise training can promote the recovery of learning and memory ability in Alzheimer's disease (AD), but the specific mechanism is still unclear. Previous studies have suggested that aquaporin-4 (AQP4)-mediated glymphatic system is an important way to clear β-amyloid (Aβ) in the brain, which is closely related to learning and memory impairment in AD. However, it remains unclear whether AQP4 regulates glymphatic clearance of Aβ which contributes to the beneficial effects of aerobic exercise in AD patients. Here, the goal of this study was to investigate the mechanisms about aerobic exercise whether AQP4 could modulate glymphatic system using APP/PS1 mice. Methods: In this study, APP/PS1 AD model mice were treated with aerobic exercise intervention through swimming exercise training for 4 weeks, and the two groups of mice were injected with AQP4 inhibition virus and empty virus, respectively. Their learning and memory abilities were assessed using behavioral tests, such as the Barnes maze and Morris water maze tests. Hippocampus was obtained from sacrificed mice and used for histological analysis. Tracer imaging of the cerebellar medullary pool was used to observed the CSF-ISF exchange, immunohistochemistry was used to detect the level of Aβ plaques in the hippocampus of mice in each group; immunoblotting was used to detect the expression of AQP4 protein; immunofluorescence co-labeling was used to detect the polarization distribution of AQP4; qRT-PCR was used to detect the transcription levels of AQP4 and its anchoring proteins. Results: The funding showed that APP/PS1 mice have learning and memory impairment, and the glymphatic system is dysfunction. Swimming training can improve the ability of the glymphatic system to clear Aβ deposition in the hippocampus by up-regulating the transcription levels of Lama1 and Dp71 in the hippocampus, reducing the depolarization distribution of AQP4 in the hippocampus, and enhancing the exchange of CSF-ISF. Thus, improves learning and memory impairment in APP/PS1 mice. Conclusions: Swimming training can rescue the function of the glymphatic system, increase the CSF-ISF exchange, promote the polarization distribution of AQP4, and reduce the deposition of Aβ in the hippocampus, thereby improving the learning and memory ability of APP/PS1 mice.